Investigating Lecturers’ and Students’ Perceptions of Oral Presentations in EFL Reading Class: A Qualitative Study at the English Education Study Program of Sriwijaya University - Fadhilah, Lulu; Pitaloka, Nova Lingga (JIIP - Jurnal Ilmiah Ilmu Pendidikan, 2025)
This study explored students’ and lecturers’ perceptions of using oral presentation to improve reading comprehension, as well as the challenges students faced and the strategies they used to overcome them. A qualitative approach was employed, and the data were collected through semi-structured interviews with ten English education students and two English lecturers. The findings revealed that students perceived oral presentations encouraged them to read more thoroughly, prepare more carefully, and gain a deeper understanding of the material. They also reported that oral presentations increased their motivation and responsibility in delivering clear and comprehensible explanations to their peers. Moreover, lecturers also perceived oral presentations as an effective way to assess students’ actual understanding and promote deeper engagement with texts. However, several challenges were also faced by students, including linguistic factors, psychological barriers such as anxiety and lack of confidence, and environmental aspects. To address these challenges, they employed various strategies, including preparation and practice (e.g., repeated reading, summarizing, and rehearsing), self-motivation strategies (e.g., positive self-talk and affirmations), and attention control techniques (e.g., maintaining eye contact, voice modulation, and using ice-breakers). This study provided recommendations for future researchers.